An unidentified harvestman Leiobunum sp. alarmingly invading Europe (Arachnida: Opiliones) - Wijnhoven, Hay; Schönhofer, Axel L.; Martens, Jochen (Arachnologische Mitteilungen, 2007)

(untitled)
Since about the year 2000 a hitherto unidentified species of the genus Leiobunum C. L. Koch, 1839, has rapidly invaded central and western Europe. Records are known from The Netherlands (probably the country of first occurrence in Europe), Germany, Austria and Switzerland. This introduced species, until now, mainly inhabits walls of buildings and rocky environments. Adults characteristically aggregate during daytime into groups of up to 1.000 individuals. The species is described and details on its present distribution, habitat preference, phenology and behaviour are presented.